Do Infant Birth Outcomes Vary Among Mothers With and Without Health Insurance Coverage in Sub-Saharan Africa? Findings from the National Health Insurance and Cash and Carry Eras in Ghana, West Africa - Romuladus Emeka Azuine, DrPH., RN; Gopal K. Singh, PhD; Sussan E. Ekejiuba, DVM, PhD; Eta Ashu, MSc; Magnus A. Azuine, PhD (Global Health and Education Projects, Inc., 2014)
Objective: The presence of multiple global health aid organizations in donor recipient countries at any point in time has led to arguments for and against aid coordination and aid pluralism. Little data, however, exist to empirically demonstrate the relationship between donor presence and longitudinal disease outcomes in donor-recipient countries. We examined the association between global health donor presence and changes in HIV/AIDS prevalence in 14 developing countries: 12 in Africa (Ethiopia, Kenya, Tanzania, Malawi, Zimbabwe, Mozambique, Rwanda, South Africa, Uganda, Zambia, Burkina Faso and Mali) and compared them with two developing countries in Asia (India and Vietnam). Methods: To conduct our analyses, we conceptualized a framework for examining global health donor presence and disease outcomes. Donor presence data were derived from Mapping the Donor Landscape in Global Health: HIV/AIDS, a report published by the Kaiser Family Foundation, Washington, DC, USA. HIV/AIDS prevalence data were obtained and analyzed from the World Health Statistics and the Demographic and Health Surveys. Percent changes in national HIV/AIDS prevalence between 2009 and 2011 in the 14 developing countries were computed and correlation coefficients between donor presence and prevalence changes were calculated. Results: Between 2009 and 2011, HIV/AIDS prevalence decreased in all but one of the 14 developing countries with the presence of 21 or more global health donors. There was about 40% overall reduction in HIV/AIDS prevalence across the 14 countries in our analyses. South Africa recorded the most reduction in HIV/AIDS prevalence (-6.7%) followed by Zambia (-6.3, %), and Mozambique (-5.7%). Ethiopia was the only country without a reduction in HIV/AIDS prevalence (+0.1%). A correlation coefficient of 0.43 implied greater reductions in HIV/AIDS prevalence associated with increased donor presence. Conclusions and Public Health Implications: Our study shows a correlation between donor presence and HIV/AIDS disease burden in 14 donor-recipient countries. Our findings indicate that increased donor presence yields quantifiable reduction in global health disease burden. Further research is needed to demonstrate whether these gains can be observed in other global health disease outcomes.